The effect of forward flushing, with permeate, on gypsum scale formation during reverse osmosis treatment of CaSO4-rich water in the absence of anti-scalant - Otto, Dietmar Norman (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng) -- Stellenbosch University, 2014.